Effect of Rectal Levodopa Administration: A Case Report - Jolanda M.J. Vogelzang; Marianne Luinstra; A. Wijnand F. Rutgers (Case Reports in Neurology, 2015)
Objective: The aim of this report is to discuss whether or not rectal levodopa administration is useful in some situations. Background: In situations where oral intake of levodopa formulations is not possible, the treatment options of Parkinson's disease patients are limited. The literature describes no or low rectal absorption of levodopa. Case Description: A patient with an ileus was unable to take oral medication. After consulting the neurologist and pharmacist, the surgeon decided to describe a rectal formulation of levodopa/carbidopa (100/25 mg) once daily. On day 3 of the therapy, 1 h after administration of the rectal formulation of levodopa/carbidopa, a blood sample was drawn. The patient was unable to take his other Parkinson medication; therefore the dose of the rectal levodopa/carbidopa was increased to 5 times a day. Results: Full control of the symptoms was not achieved, but alleviation of the most severe tremor and rigidity was seen, which was confirmed by the neurologist, nurses and patient. The levodopa concentration detected was 17 nmol/l. Compared to levodopa concentrations described in the literature (1,400-12,000 nmol/l), the concentration is very low. There are some possible explanations for the low concentration detected. The presence of a specific amino acid transport system in the rectum is not known, which could lead to no or reduced absorption. The poor rectal absorption of carbidopa leads to a higher conversion of levodopa to dopamine peripherally. Conclusions: In situations where patients are unable to take oral medication, rectal administration of levodopa/carbidopa is worth considering.